Penyuluhan Pengaruh Baby Massage Theraphy Pola Tidur Bayi Di Klinik Alisah - Adelina Fitri Tanjung; Eka Ristin Tarigan; Adriana Bangun; Achmad Zulfikar Siregar; Debora Keresya Pane; Nadiyah Salsabila; Sylvira Rianda; Vidya Desriyani; Siti Aisyah Sa’adah (STIKES Columbia Asia Medan, 2025)
Indonesian language learning at the junior high school level often faces challenges such as low student motivation, participation, and comprehension in reading, writing, and listening materials. The predominance of lecture-based methods and textbooks leads to suboptimal student engagement, especially in online or hybrid learning. This community service activity at SMP S Methodist 1 Rantau Prapat aims to enhance students’ understanding as well as teachers’ capacity through the application of interactive learning media. The media used include interactive PowerPoint, Wordwall, and H5P, which allow adaptive quizzes, writing exercises, and game-based activities. The implementation methods involve initial observation, development of interactive curriculum-based materials, socialization, teacher training, classroom implementation, and evaluation using pre-tests and post-tests. Data were collected through comprehension tests, classroom participation observations, and short interviews. The results showed a significant improvement: the students’ average post-test scores increased compared to the pre-test, with more active classroom participation in interactive quizzes and discussions. Teachers also felt more supported in delivering lessons and gained new skills in using digital media. In conclusion, the application of interactive media proved effective in improving the quality of Indonesian language learning and can serve as a sustainable model for secondary schools.